PREDICTIVE VALUE OF SOME ANTHROPOMETRIC CHARACTERISTICS ON THE SPECIFIC MOTOR TEST MAE GERI IN MACEDONIAN MEMBERS OF THE KARATE TEAM - Kenan Asani; Vujica Živković; Besnik Telai (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Karate and other martial sports are a complex whole, which includes a multitude of punches, blocks, avoidances , attitudes and movements . To overcome those elements and the karateist to be led to considerable perfectionism, it is necessary to develop a good anthropological status, to develop satisfactory conative traits and cognitive abilities, and meet certain health and social aspects. After realizing those conditions, it is necessary to bring the athlete in the ideal fitness, technical, tactical and psychological level, thus creates ideal conditions and could be superb, or to achieve great results. In this sense, as a special research interest appears the need for finding an "ideal" battery of tests that will be possible to predict important anthropological dimensions and capabilities to assess performance in karate The aim is to establish some connection between the anthropometric characteristics based on the specific motor test in mae geri for the members of Macedonia's karate team The study is performed on a sample of 30 respondents (N = 15)juniors and (N = 15) seniors many years respondents of Macedonian Karate team. . The male juniors are aged from 16 to 17 years and the seniors over 18 years. On the sample were measured 17 anthropometric tests as predictor system of variables , and a specific motor test "Maegeri", which is used as the criterion variable.